THE EXTENSIFICATION OF OPPORTUNITY ON A CORRUPTIONPRETRIAL PROCESS BY ATTORNEY GENERAL - Raja Mohamad Rozi (Widyariset, 2011)
The opportunity principle is opposite of legalistic principle. It is a duty to diverse a criminal case for public interest as called seponering. As accordingly a doctrine, attorney general has been represented by state and public interest. He implement the principle not to take a person to trial (the public prosecutor may decide conditionally or unconditionally to take a prosecution to court or not). Right now, actually problem, opportunity principle must be widely implemented on pre trial process. It is a consideration on a law enforcement impact of social tension and many others. The method is a normative-empiris on a descriptive-qualitative research which analyses qualitativedata. The result is opportunity principle can be widely into pre trial process in Criminal Justice System. It is mostly important because law enforcement to take a drive to be the greatest happiness for the great numbers. It means that not only certainty principle, but also justice for all.